A review and re‐interpretation of a group‐sequential approach to sample size re‐estimation in two‐stage trials. (2nd April 2014) - Bowden, J.; Mander, A.
<x xml:space="preserve">Abstract</x> In this paper, we review the adaptive design methodology of Li et al. (Biostatistics3:277–287) for two‐stage trials with mid‐trial sample size adjustment. We argue that it is closer in principle to a group sequential design, in spite of its obvious adaptive element. Several extensions are proposed that aim to make it even more attractive and transparent alternative to a standard (fixed sample size) trial for funding bodies to consider. These enable a cap to be put on the maximum sample size and for the trial data to be analysed using standard methods at its conclusion. The regulatory view of trials incorporating unblinded sample size re‐estimation is also discussed. © 2014 The Authors. Pharmaceutical Statistics published by John Wiley & Sons, Ltd.